Dynamics and molecular evolution of HIV-1 strains in Sicily among antiretroviral naïve patients - Tramuto, F.; Maida, C.M.; Bonura, F.; Perna, A.M.; Vitale, F. (Infection, genetics and evolution, 2013)
► We examine changes in the molecular epidemiology of HIV-1 strains in Sicily. ► Heterosexual contacts are responsible for the most part of HIV-1 non-B infections. ► In Sicily, HIV-1 epidemic is still mostly attributable to the B subtype. ► HIV-1 eterogeneity is mainly correlated to population movements and immigration influx. ► An increasing genetic diversity has been observed in the autochthonous population. HIV-1 subtype B is the most frequent strain in Sicily. To date, there is no available data about the genetic diversity of HIV-1 viral strains circulating in Sicily among antiretroviral (ARV) naïve subjects and the role of immigration as potential determinant of evolutionary dynamics of HIV-1 molecular epidemiology. For this purpose, HIV-1 polymerase (pol) sequences obtained from 155 ARV naïve individuals from 2004 to 2009 were phylogenetically analysed. The overall rate of HIV-1 non-B infections was 31.0% (n=48/155), increasing from 7.8% in 2004–2006 to 40.9% in 2009, and about one-third were identified as unique recombinant forms. CRF02_AG was the prevalent non-B clade (n=28/48, 58.3%), while subtype C-related strains were responsible for about 30% HIV-1 infections. Non-B viruses strictly associated with heterosexual transmission (85.4%) and were mostly found among immigrants (77.1%). Phylogenetic analysis of non-B sequences found in foreign-born subjects was geographically correlated to the respective country of origin. Moreover, the detection of non-B viral variants in the autochthonous population may support an increasing genetic diversity in Sicily as well as a local circulation of HIV strains also uncommon in our country. In Sicily, HIV-1 epidemic is still mostly attributable to the B subtype. Nevertheless, migration and population movements are progressively introducing novel HIV-1 subtypes causing a continuous increase of HIV-1 molecular dynamic at local level. Molecular surveillance is needed to monitor the genetic evolution of HIV-1 epidemic.